Distinct roles for ROCK1 and ROCK2 in the regulation of cell detachment - Shi, Jianjian (Nature Publishing Group, 2013)
This study, using mouse embryonic fibroblast (MEF) cells derived from ROCK1(−/−) and ROCK2(−/−) mice, is designed to dissect roles for ROCK1 and ROCK2 in regulating actin cytoskeleton reorganization induced by doxorubicin, a chemotherapeutic drug. ROCK1(−/−) MEFs exhibited improved actin cytoskeleton stability characterized by attenuated periphery actomyosin ring formation and preserved central stress fibers, associated with decreased myosin light chain 2 (MLC2) phosphorylation but preserved cofilin phosphorylation. These effects resulted in a significant reduction in cell shrinkage, detachment, and predetachment apoptosis. In contrast, ROCK2(−/−) MEFs showed increased periphery membrane folding and impaired cell adhesion, associated with reduced phosphorylation of both MLC2 and cofilin. Treatment with inhibitor of myosin (blebbistatin), inhibitor of actin polymerization (cytochalasin D), and ROCK pan-inhibitor (Y27632) confirmed the contributions of actomyosin contraction and stress fiber instability to stress-induced actin cytoskeleton reorganization. These results support a novel concept that ROCK1 is involved in destabilizing actin cytoskeleton through regulating MLC2 phosphorylation and peripheral actomyosin contraction, whereas ROCK2 is required for stabilizing actin cytoskeleton through regulating cofilin phosphorylation. Consequently, ROCK1 and ROCK2 can be functional different in regulating stress-induced stress fiber disassembly and cell detachment.